PERSEPSI NASABAH TERHADAP PENERAPAN PRINSIP 5C DALAM PENYALURAN KREDIT USAHA RAKYAT (KUR) OLEH PT. BANK RAKYAT INDONESIA (PERSERO), TBK UNIT TOMBATU, MINAHASA TENGGARA - Maria Marlyn Monulandi; Joachim N.K. Dumais; Lyndon R.J. Pangemanan (Sam Ratulangi University, 2016)
This study aims to describe the perception of consumers towards the implementation of the principle of 5C in loans of business credit (KUR) by Bank Rakyat Indonesia Tombatu Unit. Customer perception is the process of customers in selecting; managing and interpreting information received and furthermore will response to that information. 5C Principle are Character, Capacity, Capital, Condition, and Collateral. This study was conducted from March to June 2016. The implementation of research at PT. Bank Rakyat Indonesia (Persero) Tbk Tombatu Unit Southeast Minahasa Regency. The data used is primary data that interviewing the relevant customer and other customers using questionnaires, and secondary data obtained by dochmenting the data written by the BRI Tombatu Unit. The sampling method was convenience sampling method, where researchers have the freedom to choose any consumer who met as a sample. The number of respondents in this study was 75 respondents, namely the debtor / BRI customers Tombatu Unit. Analysis of the data used is descriptive analysis and Likert scale to describe the perception of consumers towards the implementation of the principle of 5C in lending business credit (KUR) by Bank Rakyat Indonesia. The research results showed that the perception of consumers towards the implementation of the principle of 5C is good with a good interpretation that is 77.68% and that means customers lonsider application of the 5C principle to all customers is good, because then the loan funds can be returned, and on one side of the BRI as lender / credit will be able to advance its business and other side, BRI customers can apply for a loan back to a time in the future.